Straight video blades are advantageous than curved blades in simulated pediatric difficult intubation - UMUROĞLU, TÜMAY (WILEY, 2014)
Background: It is still controversial which laryngoscope may be a better option in unanticipated difficult airway in pediatric patients. The aim of the present study was to compare two direct and two video-assisted laryngoscope devices for the management of difficult pediatric airway. MethodsForty-five anesthesiology residents and nurse anesthetists participated in the study. Macintosh, Miller, Storz Miller, and McGrath Mac curved laryngoscopes were used for tracheal intubation of 3-6-month Airsim Pierre Robin manikin. We compared the duration of successful intubation, number of attempts, glottic view grades, severity of dental trauma, the use of optimization maneuvers, and the difficulty of use of the devices with straight and curved laryngoscope blades. ResultsSuccessful intubation duration was significantly lower in Storz Miller device, and the number of intubation attempts was significantly higher in the Macintosh laryngoscope (P<0.01). According to the Cormack and Lehane classification, Grades 1 and 2 glottic view was 20% for Macintosh and 40% for Miller laryngoscope, while it was 100% for Storz Miller and 80% for McGrath (P<0.001). Difficulty VAS scores of Storz Miller device were significantly lower than the scores of Macintosh, Miller, and McGrath laryngoscopes (15.714.89, 34.726.44, 31.5 +/- 26.74, 33.4 +/- 26.67mm, respectively; P<0.01). The severity of dental trauma was significantly lower in Storz Miller compared with Macintosh, Miller, and McGrath laryngoscopes (0.96 +/- 1.04, 1.67 +/- 1.15, 1.38 +/- 1.05, 1.42 +/- 1.27, respectively; P<0.01). ConclusionStorz Miller laryngoscope was found to have advantages over the other laryngoscopes in regard to glottic view, duration of successful intubation, number of attempts, dental trauma severity, need for additional maneuvers, and ease of use.
Keywords: difficult airway; laryngoscopes; tracheal intubation; video laryngoscopes; straight blades; curved blades; STANDARD DIRECT LARYNGOSCOPY; AIRWAY MANAGEMENT; ROBIN-SEQUENCE; TRIAL; VIDEOLARYNGOSCOPY; MANNEQUIN; MILLER; CHILD